Technological Advancements in E-Commerce and Customer Relationship Management - A. Dhanalakshmi; Xu Hui; Roopini. R; R. Supriya (International Journal of Engineering and Management Research, 2020)
In the recent past, for any business to be successful it is essential to acquire, serve and retain customers. The number of users of commercial purposes has led to increased demand for E-Commerce in the global market. There has been a remarkable progress in E-Commerce due to globalization and technological advancements which led to sustainable quantum of business at affordable price. Technologies used in E-Commerce includes: Augmented Reality: The Future of E-Commerce Stores, Artificial Intelligence: Improving E-Commerce services and Optimizing Customer Experience, Voice Search, Chatbot, Blockchain Technology: A Faster, Safer and More Transparent used as E-Commerce Payment System, Security and Supply chain management. This paper focuses on the evolution of E-Commerce, development of CRM initiatives, leading E-Commerce companies, technological advancement in E-Commerce: E-Commerce platforms and service providers; software and tools used in E-Commerce and recent trends in E-Commerce and CRM in streamlining the CRM process thereby minimizing the cost of CRM.